(3HjGf CdhGf CdhjJg Udi Gddg Ydjg hSdes - (3GdZfjej , LGO Gddg Gdajhej GdTGaYj, CHh GdGNdGU,J (B1101 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdeYHhO hHYO ajbhd abO hbY EVWQGH cHjQ , hSDGd cKjQ ai dhf CdhjJg Udi Gddg Ydjg hSde hPdc YfO QaY CMO GdabQGA GdQGjI GdHjVGA Ch GdMeQGA s
(3BNQgG (B:s
(3hKHJ ai GdMOjK Cfg Udi Gddg Ydjg hSde CdHS YHO GdQMef Hf Yha YeGeI , hcPdc Ydi QVi Gddg Yfg , ceG eQ hgPG BNQ eG JMUd ai gPg GdChQGb GdbdjdI eY bUQ GdHGY hbdI GdEWdGY hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3ai MhGTjgG JUMjMGJs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B105 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B107s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
Keywords: (3GdJGQjNs